Inhibition of MC38 colon cancer growth by multicomponent chemoimmunotherapy with anti-IL-10R antibodies, HES-MTX nanoconjugate, depends on application of IL-12, IL-15 or IL-18 secreting dendritic cell vaccines - Węgierek-Ciura, Katarzyna; Mierzejewska, Jagoda; Szczygieł, Agnieszka; Rossowska, Joanna; Wróblewska, Anna; Świtalska, Marta; Goszczyński, Tomasz M.; Szermer-Olearnik, Bożena; Pajtasz-Piasecka, Elżbieta (Frontiers in Immunology, 2023)
Background: The tumor microenvironment (TME) provides a conducive environment for the growth and survival of tumors. Negative factors present in TME, such as IL-10, may limit the effectiveness of cellular vaccines based on dendritic cells, therefore, it is important to control its effect. The influence of IL-10 on immune cells can be abolished e.g., by using antibodies against the receptor for this cytokine - anti-IL-10R. Furthermore, the anticancer activity of cellular vaccines can be enhanced by modifying them to produce proinflammatory cytokines, such as IL-12, IL-15 or IL-18. Additionally, an immunomodulatory dose of methotrexate and hydroxyethyl starch (HES-MTX) nanoconjugate may stimulate effector immune cells and eliminate regulatory T cells, which should enhance the antitumor action of immunotherapy based on DC vaccines. The main aim of our study was to determine whether the HES-MTX administered before immunotherapy with antiy-IL-10R antibodies would change the effect of vaccines based on dendritic cells overproducing IL-12, IL-15, or IL-18. Methods: The activity of modified DCs was checked in two therapeutic protocols - immunotherapy with the addition of anti-IL10R antibodies and chemoimmunotherapy with HES-MTX and anti-IL10R antibodies. The inhibition of tumor growth and the effectiveness of the therapy in inducing a specific antitumor response were determined by analyzing lymphoid and myeloid cell populations in tumor nodules, and the activity of restimulated splenocytes. Results and Conclusions: Using the HES-MTX nanoconjugate before immunotherapy based on multiple administrations of anti-IL-10R antibodies and cellular vaccines capable of overproducing proinflammatory cytokines IL-12, IL-15 or IL-18 created optimal conditions for the effective action of these vaccines in murine colon carcinoma MC38 model. The applied chemoimmunotherapy caused the highest inhibition of tumor growth in the group receiving DC/IL-15/IL-15Rα/TAg + DC/IL-18/TAg at the level of 72.4%. The use of cellular vaccines resulted in cytotoxic activity increase in both immuno- or chemoimmunotherapy. However, the greatest potential was observed both in tumor tissue and splenocytes obtained from mice receiving two- or three-component vaccines in the course of combined application. Thus, the designed treatment schedule may be promising in anticancer therapy.